Political Gimmicks on Social Media in the 2024 Indonesian Presidential Election - Aminulloh, Akhirul; Ananda, Kun Sila; Anzari, Prawinda Putri; Fianto, Latif; Qorib, Fathul (Universitas Negeri Surabaya, 2025)
Political gimmicks have become a trendy yet controversial term in the 2024 presidential election contest. Instead of conveying the vision and mission of presidential candidates, political gimmicks only present and show skin packaging rather than substance. This research aims to reveal the practices of political gimmicks on social media in the 2024 Indonesian presidential election contestation using critical discourse analysis as a method. This method is used to reveal ideology and power relations from gimmicks that appear on social media. Data collection in this study used documentation techniques, in the form of data collection from social media X during the period December 2023 - February 2024. The study's findings demonstrate that the Republic of Indonesia's 2024 presidential and vice-presidential candidates' political communication efforts on social media X are mired in creating symbols disconnected from meaningful and substantial ideas. Drawing on Erving Goffman’s dramaturgical theory, this study frames political gimmicks as